2015
DOI: 10.1108/f-01-2014-0009
|View full text |Cite
|
Sign up to set email alerts
|

Research on nursing unit layouts: an integrative review

Abstract: STRUCTURED ABSTRACTPurpose: To present an integrative review of the research studies on nursing unit layouts.Methodology: Studies selected for review were published between 1956 and 2014. For the purpose of this review, a framework for integrative review was developed using research orientations. The three primary dimensions-technical, psychological, and social-of the designed environment and various combinations of these dimensions were used to define the research orientations of these studies.Findings: Of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…Elf, Nordin, Wijk, & McKee, 2017;Codinhoto, Tzortzopoulos, Kagioglou, Aouad, & Cooper, 2009;Ulrich, Berry, Quan, & Parish, 2010;Durmisevic & Ciftcioglu, 2010;Haq & Luo, 2012;Rashid, 2015). The purpose of these models is varied and influenced by diverse disciplinary foundations.…”
Section: Preliminary Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Elf, Nordin, Wijk, & McKee, 2017;Codinhoto, Tzortzopoulos, Kagioglou, Aouad, & Cooper, 2009;Ulrich, Berry, Quan, & Parish, 2010;Durmisevic & Ciftcioglu, 2010;Haq & Luo, 2012;Rashid, 2015). The purpose of these models is varied and influenced by diverse disciplinary foundations.…”
Section: Preliminary Conceptual Frameworkmentioning
confidence: 99%
“…Researchers, in this case, are careful in terms of suggesting design implications. For example, the (dis)advantages of (de)centralized nursing unit layouts has to be discussed by staff and/or considered from the patients' point of view (Pati, Harvey, Redden, Summers, & Pati, 2015;Rashid, 2015); the optimal number of beds in a patient's room requires further studies (Chaudhury, Mahmood, & Valente, 2005;Van de Glind et al, 2007), while Yildirim and Yalcin (2016) discuss the benefits of single rooms. Studies indicated that using carpets, or other low-impact flooring solutions, did not show significant differences in reducing the risk of falls compared with a vinyl flooring (Hanger, 2017;Warren & Hanger, 2013); while Lachance et al's (2017) review concluded that compliant flooring was a promising strategy for preventing fall-related injuries.…”
Section: Final E-o-h Frameworkmentioning
confidence: 99%
“…The results of this study suggest that communication network data may also be an important consideration to support desirable communication patterns that have the potential to reduce the number of patient falls. As Rashid (2015) notes: Unit layouts can do a great deal to encourage communication and collaboration by eliminating visual and physical barriers. Conversely, they can all too easily disrupt existing relationships by imposing unnecessary barriers.…”
Section: Discussionmentioning
confidence: 99%
“…These authors used TVI to compare various unit shapes and concluded that radial and double corridor units had the best visibility. However, as Rashid (2015) noted, TVI methodology only uses geometry and omits the human factors involved. Space Syntax analysis is another technique that could be useful to identify sight lines, as well as travel paths, under different unit designs, but may have some of the same limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The overall layout of a nursing unit is an important environmental design feature because it implies spatial relevance that impacts clinical practice (Rashid, 2015). An open layout may positively affect patients’ sense of safety and security as they can see others on the floor, facilitate patients’ need for social interaction, and provide a positive distraction for patients (Rashid, 2015; Wang & Pukszta, 2018).…”
mentioning
confidence: 99%